Pengaruh Kompetensi Sumber Daya Manusia dan Tarif Air terhadap Profitabilitas pada Perusahaan Umum Daerah Air Minum Muara Tirta Kota Gorontalo - Sitti Rahmatya Bilalea; Mattoasi; Zulkifli Bokiu (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to examine the impact of human resource competence and water tariffs on profitability at the Muara Tirta Regional Public Water Company, Gorontalo City. This research is quantitative research. The data sources used are primary data collected through a questionnaire distributed to 71 respondents, who are employees knowledgeable about finance, utilizing purposive sampling. The data analysis technique involves descriptive quantitative analysis using t-statistic tests, f-statistic tests, and coefficient of determination tests (Adjusted R Square) using IBM SPSS 20 for Windows. The results indicate that human resource competence has a positive and significant impact on profitability, water tariffs have a positive and significant impact on profitability, and both human resource competence and water tariffs simultaneously have a positive and significant impact on profitability at the Muara Tirta Reional Public Water Company, Gorontalo City, with a coefficient of determination value of 21.1%. The remaining 78.9% is explained by other variables not examined in this research.